2007
DOI: 10.1002/mop.22630
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐coupled Hilbert spiral resonator for bandpass filter design

Abstract: The modified cross-coupled spiral resonators with Hilbert configuration are introduced for a large coupling coefficient in this article. For comparison, the conventional cross-coupled spiral resonators are fabricated and measured herein. To obtain low insertion loss (Ϫ0.27 dB), high out-of-band rejection level (Ϫ19.5 dB) and wider FBW (50.9%), the filter of simplified CCSR-H is proposed. Results included surface current distribution and frequency responses are presented and discussed. ABSTRACT: A simple method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…From the initial curve of branch (a) of Figure 1, branches (b), (c), (d), and (e) can be formed relatively. As the iteration order of the curve increases, the Hilbert fractal curve may space-fill the patch [11,15].…”
Section: Hilbert Fractal Geometry and Step Impedance Resonatormentioning
confidence: 99%
“…From the initial curve of branch (a) of Figure 1, branches (b), (c), (d), and (e) can be formed relatively. As the iteration order of the curve increases, the Hilbert fractal curve may space-fill the patch [11,15].…”
Section: Hilbert Fractal Geometry and Step Impedance Resonatormentioning
confidence: 99%
“…Since then, research work in this field has shown a dramatic increase. In this respect, various fractal geometries have been applied to design compact single-band and dual-band microstrip BPFs (Ahmed, 2012;Alqaisy, Ali, Chakrabarty, & Hock, 2013;Barra, 2004;Chen & Lin, 2011;Chen, Weng, Jiao, & Zhang, 2007;Crnojevic-Bengin, Radonic, & Jokanovic, 2006;Feng, Ming, & Hui, 2012;Ghatak, Pal, & Sarkar, 2013;Li et al, 2012;Liu, Chien, Lu, Chen, & Lin, 2007;Liu et al, 2012;Mezaal, 2009;Mezaal, Eyyuboglu, & Ali, 2013a, 2013b.…”
Section: Introductionmentioning
confidence: 98%
“…Hilbert fractal geometry has been harnessed as a defected ground structure in the design of a microstrip lowpass filter for L-band communication application . Typical and simplified cross-coupled spiral resonators with Hilbert configuration were introduced by Liu et al (2007) for a huge coupling factor with comparison between each other. Narrow band dual resonator microstrip BPFs based on Hilbert fractal curves have been proposed for wireless application as in Mezaal (2009) within ISM band at fundamental frequency of 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the improved model, a compact L-band microstrip low-pass filter with periodic DGS was designed and studied. Typical and simplified cross-coupled spiral resonators with Hilbert configurations have been stated in [10] for a large coupling coefficient with comparison between each other. All of designs introduced in [10] have low insertion loss, high out-of-band rejection level and wider band frequency responses.…”
Section: Introductionmentioning
confidence: 99%
“…Typical and simplified cross-coupled spiral resonators with Hilbert configurations have been stated in [10] for a large coupling coefficient with comparison between each other. All of designs introduced in [10] have low insertion loss, high out-of-band rejection level and wider band frequency responses. Moreover, surface current distributions simulated by IE3D EM software package have been used to analyze the coupling regions in spiral and Hilbert configurations.…”
Section: Introductionmentioning
confidence: 99%